2015
DOI: 10.1103/physreve.91.023004
|View full text |Cite
|
Sign up to set email alerts
|

Observations of spontaneous oscillations in simple two-fluid networks

Abstract: We investigate the laminar flow of two-fluid mixtures inside a simple network of inter-connected tubes. The fluid system is comprised of two miscible Newtonian fluids of different viscosity which do not mix and remain as nearly distinct phases. Downstream of a diverging network junction the two fluids do not necessarily split in equal fraction and thus heterogeneity is introduced into network. We find that in the simplest network, a single loop with one inlet and one outlet, under steady inlet conditions the f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…Oscillations similar to our finding were recently discovered in a stratified flow of two miscible liquids in a narrowing loop [32]. It suggests a possible existence of a common mechanism of oscillations caused by flow of complex fluids through parallel, narrowing ducts.…”
Section: Discussionsupporting
confidence: 90%
“…Oscillations similar to our finding were recently discovered in a stratified flow of two miscible liquids in a narrowing loop [32]. It suggests a possible existence of a common mechanism of oscillations caused by flow of complex fluids through parallel, narrowing ducts.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are consistent with experimental results reported by Storey et al. ( 2015 ). They conducted experiments involving mixtures of two fluids in slightly different network geometries and found that imposing flux boundary conditions produced a larger region of instability than imposing pressure boundary conditions.…”
Section: Characterising the Steady And Dynamic Behaviours Of A Three-...supporting
confidence: 94%
“…This approach has proved fruitful in the past. Prior theoretical work using similar network models, but different constitutive laws for stratified flow of Newtonian fluids with different viscosity (Karst et al 2014) led to experiments which confirmed the existence of oscillations (Storey et al 2015). Here, however, the predictions of observable oscillatory behavior with blood flow occur over a relatively narrow range of parameters.…”
Section: Discussionmentioning
confidence: 55%